2005
DOI: 10.1248/bpb.28.1722
|View full text |Cite
|
Sign up to set email alerts
|

The in Vivo Effect of Cordyceps sinensis Mycelium on Plasma Corticosterone Level in Male Mouse

Abstract: Cordyceps sinensis (CS) is an Ascomycetes fungus parasitic to Lepidoptera larvae, and has long been used as medicine to treat many illnesses and promote longevity in Chinese society.1,2) Previous investigations have shown that CS has many pharmacological activities such as reducing mean arterial pressure, 3) preventing cholesterol deposition in aorta, 4) and inducing tumor programmed cell death. [5][6][7][8] Moreover, reports have also demonstrated that CS can suppress tumor cell growth, modulate immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It was showed that C. sinensis stimulates E2 production in human granulosa-lutein cells (GLCs) by upregulating the expression of several key enzymes, especially StAR and aromatase, making it a brilliant candidate for increasing the fecundity of women ( Huang B M et al, 2004 ). Moreover, C. sinensis and its fractions have been reported to induce in vivo plasma corticosterone levels in immature and mature mice ( Leu et al, 2005 ). Besides, C. sinensis could improve the function of reproduction and testis morphology in mice ( Jin and Guo, 2006 ).…”
Section: Pharmacological Potential Of Cordyceps Spmentioning
confidence: 99%
“…It was showed that C. sinensis stimulates E2 production in human granulosa-lutein cells (GLCs) by upregulating the expression of several key enzymes, especially StAR and aromatase, making it a brilliant candidate for increasing the fecundity of women ( Huang B M et al, 2004 ). Moreover, C. sinensis and its fractions have been reported to induce in vivo plasma corticosterone levels in immature and mature mice ( Leu et al, 2005 ). Besides, C. sinensis could improve the function of reproduction and testis morphology in mice ( Jin and Guo, 2006 ).…”
Section: Pharmacological Potential Of Cordyceps Spmentioning
confidence: 99%
“…The fermented mycelia of C. sinensis has been used popularly as a nutritious or health food in China and Japan, because it has a similar pharmacological efficacy to the natural Cordyceps which is scarce and expensive (Hsu et al, 2002;Li et al, 2001b;Zhu et al, 1998aZhu et al, , 1998b. Furthermore, there have been many reports describing the various biological activities of C. sinensis (Leu et al, 2005;Li et al, 2001a;2001b;Yamaguchi et al, 2000;Zhang et al, 2006;, but only a few have identified the proteins responsible for its activity (Chiou et al, 2000;Ye et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An animal study and an in vitro study reported that cordyceps extract has a stimulatory effect on the adrenal gland and increased the corticosterone level. (21,22) However, no clinical case reports or studies have reported on its corticosteroidal activity.…”
Section: Cordyceps (Cordyceps Sinensis Dong Chong Xia Cao 冬虫夏草)mentioning
confidence: 99%